Dosimetric measurement of testicular dose for colorectal cancer using optically-stimulated luminescent dosimeters in radiotherapy. (July 2020) - Lu, C.C.; Wang, F.N.; Lin, H.H.; Hsu, C.H.; Lin, J.P.; Lai, L.H.
Abstract: In radiotherapy for colorectal cancer, control of the testicular dose in young patients is important, as exposure of the testis could lead to temporary or permanent infertility. Although the testis is located out of the treatment field in patients receiving radiotherapy, it is inevitably exposed to scattered radiation resulting from the interaction between primary beams and patients and collimators. In this study, dosimeters were used to measure the testicular dose with and without testicular shielding to verify the effect of shielding. Anthropomorphic phantoms representing a human were used to estimate the doses absorbed in testicular and whole-body studies. The anthropomorphic phantom was irradiated according to the treatment protocol for colorectal cancer. Measurements were made using optically-stimulated luminescent dosimeters (OSLDs), composed of carbon-doped aluminum oxide, with characteristics suitable for radiotherapy dosimetry studies. A set of OSLDs was placed on a testicular phantom, attached to the lower edge of the pelvis of the anthropomorphic phantom. Dosimeters were also placed surround a testicular shielding to estimate the scattered dose. The testicular dose was 60–85 cGy when a dose of 4500 cGy was delivered to the whole pelvic area, while the dose was reduced to 34–50 cGy when testicular shielding was used. In addition, the increase in the surrounding scattered dose due to the testicular shielding was not significant. Highlights: Testicular shielding can reduce the testicular dose from 60 - 85 to 34–50 cGy. For men of reproductive age, use of testicular shielding was necessary. Increase in the peripheral dose from testicular shielding was not significant.